Fungsi Pengawasan Dewan Perwakilan Rakyat Daerah Dalam Tata Kelola Pemerintahan Daerah Yang Bersih Dan Bebas Korupsi (Studi Kasus Di DPRK Aceh Timur) - Hamdani Hamdani; Faisal Akbar; Mirza Nasution; M Ekaputra (Iuris Studia: Jurnal Kajian Hukum, 2021)
Supervision conducted by the Regional People's Representative Council, one of which is the performance carried out by the Regional Government Apparatus, namely by supervising the regional / regional expenditure budget that has been established and run by the regional government apparatus. As one of the areas studied is the East Aceh Regional Government in Aceh Province. Based on the description of the background above, the problem can be formulated in this study as follows: 1. How is the position of the Regional Representative Council in the structure of the East Aceh Regional Government? 2. How about the form of supervision in terms of preventing the deviation of the use of regional budgets carried out by the East Aceh Regional Government Apparatus? 3. How the effectiveness of supervision carried out by the East Aceh Regional Representative Council in regional government governance is clean and free of corruption? The research method used in this study is a type of normative legal research, which is supported by primary and secondary data sources, and analysis Qualitatively. The results of the research and discussion, namely the position of the Regional People's Representative Council in the structure of the East Aceh Regional Government is a representative institution in the regions, and at the same time as an element of organizers of the regional government. The form of supervision in terms of preventing irregularities in the use of regional budgets, namely by determining the targets and standards for supervision relating to concrete matters such as monitoring and observing the implementation of projects carried out in a budget year, and further responding to public complaints to the occurrence of irregularities The use of regional budgets. Supervision carried out by the East Aceh Regional Representative Council in regional government governance that is clean and free of corruption is still not effective due to time limitations and because in addition to overseeing activities in the field also serve the community..